PERAN BUMDES DALAM PEMBERDAYAAN MASYARAKAT DI DESA BANGUN JAYA KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Nuraini Siboro (Jurnal Ilmiah Cano Ekonomos, 2023)
This research focused on: (1) How is community empowerment before BUMDes exist Bangun Jaya Village? (2) How is community empowerment after BUMDes existed in Bangun Jaya Village, (3) What is the role of BUMDes in community empowerment in Bangun Jaya Village?. The aims of this research were: (1) To find out the community empowerment before BUMDes exist in Bangun Jaya Village. (2) To find out the community empowerment after BUMDes existed in Bangun Jaya Village. (3) To find out the role of BUMDes in community empowerment in Bangun Jaya Village. This research used qualitative research methods with the type of research was field research. The researcher used purposive technique to determine the informants. Data collection techniques in this research were observation, interviews and documentation. The data analysis technique used data reduction, data presentation, and drawing conclusions. The validity of the data used source triangulation techniques. This research resulted in: (1) Community empowerment before the existence of BUMDes had been running well, namely through the PKK program, Posyandu and supporting UMKM, (2) BUMDes carried out several programs such as: Saving and Loan Business, and Mini Market. The existence of BUMDes could open the opportunities as an effort to minimize unemployment and could increase PADes income (village original income), (3) The role of BUMDes towards community empowerment in Bangun Jaya Village as a way to explore the potential in Bangun Jaya Village,to strengthen the existence of economic turnover and to increase public enthusiasm for entrepreneurship.